Student Perceptions of Online-Based Learning During the Covid 19 Pandemic - R, Zubaidah; Munaldus, Munaldus; Fitriawan, Dona; Bistari, Bistari (Media Pendidikan Matematika, 2022)
Learning in a network or online is the best solution taken to avoid the spread of the corona virus during the covid 19 pandemic. The objectives of the research are (1) to obtain an appropriate instrument to be used to measure student perceptions, (b) to describe student perceptions in terms of Interactivity, Independence, Accessbillity and Enrichment aspects. The form of the research is descriptive qualitative. The conclusions of the research are (a) The instrument for measuring student perceptions of online-based learning in terms of the validity of panelists' suitability, item validity, panelist suitability reliability and item reliability is classified as feasible, (b) Student perceptions of online learning in terms of Interactivity, Independence and Enrichment aspects are classified as positive, (c) students' perceptions of online learning in terms of accessibility aspects are classified as negative, (d) student perceptions of the Interactivity aspect, active items providing input or responding to group presentation results in online lectures are classified as negative, (e) Perceptions of the Independence aspect Items are more diligent in studying in online lectures compared to face-to-face lectures is classified as negative. Perceptions of the Accessbillity aspect, the item did not experience difficulties in understanding lecture material online and lectures were still carried out online even though the Covid situation was normal and was classified as negative.